Comparison of in-plane and out-of-plane failure modes of masonry arch bridges using discontinuum analysis - Pulatsu, Bora (2019)
This research aims to provide a better understanding of the structural behavior of masonry arch bridges using advanced modeling strategies. Two main contributions are achieved in this article; first, triggering mechanisms for the out of plane failure of spandrel walls are established; second, the influence of soil backfill on the behavior and strength of the bridges is presented through a comprehensive parametric study. Here, masonry arch bridges are modeled using a discontinuum approach, composed of discrete blocks, including also a continuum mesh to replicate infill material, adopting a framework of discrete element modeling. The equations of motion for each block are solved by an explicit finite-difference method, using the commercial software 3DEC. The results of the preliminary analyses are compared with analytical solutions and limit state analysis for validation purposes. Different arch bridge models, representing common geometrical properties in the northwest Iberian Peninsula are analyzed. Transverse effects, damage patterns and collapse mechanisms are discussed under different types of loading. The analysis demonstrated the severe capacity reduction due to spandrel wall failures and the importance of soil backfill in results, only possible by taking advantage of the performed numerical modeling strategy.